Physical Activity in Solid Organ Transplant Recipients: Preliminary Results of the Italian Project - Giovanni Mosconi; Vania Cuna; Maddalena Tonioli; Valentina Totti; Giulio S. Roi; Patrizio Sarto; Sergio Stefoni; Manuela Trerotola; Alessandro Nanni Costa (Karger Publishers, 2014)
Background/Aims: The role of physical activity in transplanted patients is often underestimated. We discuss the Italian National Transplant Centre experience, which started in 2008 studying transplanted patients involved in sports activities. The study was then developed through a model of cooperation between surgeons, sports physicians and exercise specialists. Methods: A multicentre study was realized in 120 transplanted patients of which 60 treated with supervised physical activity (three sessions/week of aerobic and strengthening exercises) and 60 controls. We present the results of the first 26 patients (16 males, 10 females; 47.8±10.0 years; 21 kidney, 5 liver transplanted; time from transplant 2.3±1.4 years) who completed 12 months of supervised physical activity. Results: Data showed an increase of peak aerobic power (t=4.535; PConclusion: These preliminary results confirm the positive effects of supervised physical exercise. It can be considered as an input to promote other detailed exercise protocols.